Pediatric post-thrombotic syndrome in children: Toward the development of a new diagnostic and evaluative measurement tool. Issue 144 (August 2016) - Avila, M.L.; Brandão, L.R.; Williams, S.; Ward, L.C.; Montoya, M.I.; Stinson, J.; Kiss, A.; Lara-Corrales, I.; Feldman, B.M.
Abstract: Objective: Our goal was to conduct the item generation and piloting phases of a new discriminative and evaluative tool for pediatric post-thrombotic syndrome. Methods: We followed a formative model for the development of the tool, focusing on the signs/symptoms (items) that define post-thrombotic syndrome. For item generation, pediatric thrombosis experts and subjects diagnosed with extremity post-thrombotic syndrome during childhood nominated items. In the piloting phase, items were cross-sectionally measured in children with limb deep vein thrombosis to examine item performance. Result: Twenty-three experts and 16 subjects listed 34 items, which were then measured in 140 subjects with previous diagnosis of limb deep vein thrombosis (70 upper extremity and 70 lower extremity). The items with strongest correlation with post-thrombotic syndrome severity and largest area under the curve were pain (in older children), paresthesia, and swollen limb for the upper extremity group, and pain (in older children), tired limb, heaviness, tightness and paresthesia for the lower extremity group. Conclusion: The diagnostic properties of the items and their correlations with post-thrombotic syndrome severity varied according to the assessed venous territory. The information gathered in this study will help experts decide which item should be considered for inclusion in the new tool. Highlights: Physicians and patients proposed the signs/symptoms for measuring pediatric PTS. PTS signs/symptoms differed in diagnostic performance between upper and lower limbs. Standardization of the measurement techniques will allow replicating the findings. The reported data provide the foundation for a new pediatric PTS measurement tool.